ISSUES OF APPLICATION OF COMPETITIVE STRATEGIES IN TEXTILE ENTERPRISES - Abdurakhmonova Shohida Ravshanovna (Scholar Express Journals, 2021)
The article proposes proposals for ensuring competitive advantages in textile enterprises and developing competitive strategies. The essence of the concepts of competition, competitiveness is determined. and the management of the competitiveness of textile enterprises. The process of choosing competitive strategies is described.
Keywords: Competition; competitiveness; competitiveness management; competitive advantages